Home and (un)belonging in October by Zoë Wicomb. (1st September 2016) - Jacobs, J. U.
ABSTRACT: Zoë Wicomb's third novel, October (2014), provides the most searching revision of the notion of home in contemporary South African fiction. Taking as its point of departure the epigraphs from Tony Morrison's novel, Home (2012), and Marilynne Robinson's similarly named novel, Home (2009), this article examines the intertextuality of these fictional works with Wicomb's novel in the light of the themes of home and belonging. The traditional, or "thick" notions of home and belonging – also in the wider contexts of community and home country – are theorised with reference to the postcolonialist/postnationalist scholars, Brah, Hedetoft and Hjort, and George. "Home", it is argued, is an ambiguous concept, defined not only in terms of inclusion but also of exclusion, and non-belonging, as therefore are also community and home country. The neuro-anthropologist, John S. Allen, provides perhaps the most comprehensive account in recent literature of the evolution of the home sense in human beings. Non-belonging is different from un belonging, the article further argues: un belonging – expulsion from a secure sense of home, is explained with reference to the work of Freud, Martin and Mohanty, and Bhabha. The article then presents an analysis of the situation of Mercia Murray, the South African-born protagonist of Wicomb's October, showing first her unhoming in exile in Glasgow, and how as an expatriate she lives "between worlds" (Chambers). It further analyses her homecoming to her brother's house in Kliprand in Namaqualand, and her further unhoming as, through a range of discourses – literary criticism, memoir and intertextuality – the narrative traces her estrangement and alienation, and that of her brother Jake, from family home and community, back to the authoritarian figure of her schoolmaster father. The essay considers the various tropes for being at home that the reader is offered in the course of the narrative.